2020
DOI: 10.1111/ijcp.13920
|View full text |Cite
|
Sign up to set email alerts
|

Frequent witnessing to interparental conflict and low parental availability for leisure‐time is associated with dysfunctional voiding in primary school children

Abstract: Aim Aspects of parenting are an under‐investigated topic amongst children with voiding complaints. We aimed to investigate the association between voiding complaints amongst children and two specific parenting‐related behaviours: 1) parental availability during the child's leisure time and 2) frequency of witnessing interparental conflict. Material and Method Children aged between 6 and 11 years with their parents were the participants. Two survey forms and informed consent form were sent to potential particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Family Systems Theory considers the family as a whole, and holds that conflict between any two family members also affects other family members (Cox and Paley, 2003). Previous reports have shown that nearly a quarter of children witnessed one or more parental conflicts in the past month (Cihan and Ünalan, 2020). As important members of the family, children are particularly vulnerable to conflict between family members (e.g., perceived conflict between parents).…”
Section: Introductionmentioning
confidence: 99%
“…Family Systems Theory considers the family as a whole, and holds that conflict between any two family members also affects other family members (Cox and Paley, 2003). Previous reports have shown that nearly a quarter of children witnessed one or more parental conflicts in the past month (Cihan and Ünalan, 2020). As important members of the family, children are particularly vulnerable to conflict between family members (e.g., perceived conflict between parents).…”
Section: Introductionmentioning
confidence: 99%